AUDIT OPERASIONAL ATAS PERSEDIAAN BARANG DALAM MENINGKATKAN EFEKTIVITAS DAN EFESIENSI PADA PERUSAHAAN PT SECMA ENERGY CELL - Fadilah, Ulil; Nur, Basyiruddin (Politeknik Negeri Lhokseumawe, 2023)
The purpose of this study is to determine the Operational Audit of Inventory of Goods in Improving Effectiveness and Efficiency at PT Secma Energy Cell. The research method used is descriptive qualitative method with a case study approach, the type of data used in this research is primary and secondary data obtained directly from PT Secma Energy cell, while secondary data is obtained from articles, books, scientific journals and other relevant sources, the sampling method used is purposive sampling (judgment sampling). sik East Java – Indonesia. Research results at PT. Secma Energy Cell points out that inventory operational audits are running well, with audit functions that include approval, verification, and evaluation, inventory operational audits are also carried out at a low cost and efficiently so as to avoid unwanted risks, so as to be able to increase effectiveness and efficiency at PT Secma Energy cell.Keywords: operational audit, inventory, effectiveness, efficiency